Where Have all the Antibiotics Gone? - Julian Davies (Canadian Journal of Infectious Diseases and Medical Microbiology)
The discovery of antibiotics some 60 years ago was anticipated to herald the end of infectious diseases. However, microbial evolution and genetic jugglery have dispelled this notion; the constant increase in the appearance of resistant strains has not been matched by the introduction of new therapeutic agents. On the contrary, the dire need for novel antibiotics has coincided with a reduction in antibiotic discovery programs in the pharmaceutical industry. As a result, the treatment of microbial diseases has reached a point where many infections are essentially untreatable by the antimicrobial agents currently available. At the present time, numerous initiatives are being undertaken by physicians and by governments in an attempt to redress this situation. In addition, alternative approaches to antibiotics for the treatment of infectious diseases are being explored intensively.